VaxcineTM: an oil-based adjuvant for influenza vaccines - Rosely Cabette Barbosa Alves; Roger Randal Charles New; Gabrielle Ribeiro Andrade; Rita Maria Zucatelli Mendonça; Osvaldo Augusto Brasil Esteves Sant'Anna; Dalva Assunção Portari Mancini; Silvio Marciano da Silva-Junior; Marta de Oliveira Domingos (Memorias do Instituto Oswaldo Cruz, 2011)
Vaccination is the method of choice for the prevention of influenza infection. However, the quantity of the antigen available, especially in the case of pandemics, often fails to meet the global demand. However, improved adjuvants can overcome this problem. Preliminary results obtained in this study revealed that one year after a single subcutaneous immunisation with influenza A H3N2 virus in an oil-based carrier, VaxcineTM, outbreed mice produced a high immunoglobulin G response that lasted for up to one year and exhibited less variation in titre compared with the response of the control group treated with alum. The haemagglutination-inhibition titres induced by VaxcineTM were also higher than those generated by alum. These data indicate that VaxcineTM is a good adjuvant candidate for seasonal influenza vaccines.